Residues and dissipation of imidacloprid in grape berries and soil in an arid zone (Bioagro, 2025)
The widespread use of neonicotinoid insecticides in crop management can generate residues with negative impacts on consumer health. The objective was to determine residues and the dissipation of imidacloprid in grape berries and soil following applications of the insecticide imidacloprid at four doses and in two forms in an arid area. The research was conducted on a ´Red Globe´ grape plantation located in Arequipa, Peru. The treatments consisted of applying four doses of a commercial formulation of the insecticide imidacloprid (0.5, 1.0, 1.5, and 2.0 L·ha-1) using two application forms (foliar spray and plant collar drench). Eight treatments were evaluated in a DBCA design, with three replicates per treatment and 24 experimental units. The commercial insecticide used was Diprid 350EC, applied 35 days before the harvest of the bunches. Imidacloprid was determined by HPLC in berries and soil obtained 1, 7, 14, 21, 28, and 35 days after the initial application of the insecticide. In grape berries, the treatments indicated did not generate imidacloprid values above the MRLs. Foliar application resulted in higher imidacloprid residues than drenching, regardless of the dose administered. The ingestion of grape berries with imidacloprid residues in the treatments indicated does not pose any health risk. In the soil, none of the treatments exceeded the investigated sanitary level of imidacloprid; therefore, accidental contact with these soils will not pose any health risk to humans.
Keywords: Neonicotinoid insecticide; residuality; toxicity; Vitis vinifera